Proyecto de factibilidad para la implementación de una microempresa productora y comercializadora de snacks de plátano en empaque de 28gr, en la ciudad de Morona, cantón Morona, provincia de Morona Santiago, para el año 2017 - Chimbo Zhunio, Norma Zoraida (2017)
The present investigation is faced with the lack of undertakings in the Morona canton and the Morona Santiago province and also to take advantage of an agricultural product such as bananas, whose production does not have the added value necessary to generate higher incomes for this sector. Well I know that seeks to promote the development of a new product where the knowledge of human talent is seen as a socioeconomic generator that increases the levels of competitiveness in the canton, province and country, especially so that in the future, it helps to reduce deficits in the trade balance that is getting worse, through the entry of new currencies to the Ecuadorian economy. Therefore, through this project has been proposed as a general objective, determine the feasibility for the implementation of a micro-company producer and marketer of banana snacks of 28gr, in the city of Morona, Morona Canton, Province of Morona Santiago, for the year 2017. In order to achieve the general objective, it was necessary to execute different specific objectives and, in summary, make reference to the following studies: market, technical, administrative, economic-financial and financial evaluation. To achieve the proposed objective, different methods were used; it was used for the process of determining the proposal based on the problem posed. The deductive method used to obtain general information about the existence of companies engaged in the production of products based on plantain, as well as knowing the products that can be made. The statistical method was used in the tabulation and analysis of the surveys. Others were used techniques such as the survey, which was applied to a representative sample of the families of the Morona canton, said sample was 372 families, likewise the direct observation was used to verify in a real way the places where the banana, in order to know and feel the product and prices. Sample data will be taken from the population belonging to the Morona canton. Among the results of the research process, it can be mentioned: The market study resulted in an unsatisfied demand 626,545 units of 28gr. Banana snacks, an installed capacity of 580,800 units of the aforementioned product was established, thus covering 92.70 % of unsatisfied demand, in year 1, and in year 10, 72.43%. Likewise, a retail price of 25 is determined, which increases up to 30 cents in year 10. Then we proceeded to perform the technical study of the project which allowed us to verify what is the process for the preparation of the product, where the company is located geographically and other technical data that intervened in the project Afterwards, the Administrative study was carried out, focusing mainly on Legal aspects for the operation of the company. The Financial Study that collects all the numerical information of the company, such as: the investments 57,843.76 dollars in which the fixed assets: land, house, adjustments, civil works, equipment, tools and others. 40% of the total investment will be financed by the Author 60% through a pacific bank loan. Capital recovers in 2 years, 10 months and 7 days. The cost for the total for the first year is of 107,521.41 dollars and the income for the same year is of 139,177.84 dollars and the net profit of 19,247.41. In the financial evaluation, a NPV of 84,759.49 is determined, the IRR is of 41.16%, the cost benefit ratio is calculated in 1.25; capital recovers in 2 years, 6 months and 11 days, the project to experience an increase in costs of 15.40% and a decrease in revenues of 11.85%; It will not be affected. The work is concluded, mentioning the feasibility of executing the project since this is demonstrated by the different financial indicators, that is, a positive NPV is obtained, the IRR is higher than the cost of credit, in the cost benefit ratio for each dollar invested 25 cents of return will be obtained, the period of capital recovery is less than the years of the project's useful life and the sensitivity analysis results in a value less than 1, both with an increase in costs and with a decrease in income.